Globalization: Implications for firms in Germany - Holger Görg; Aoife Hanley (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2017)
[Introduction ...] This paper, however, is not about evaluating whether or not Germany has, on aggregate, done well out of globalization. Rather, we dig deeper into the economy and acknowledge the fact that it is not countries that trade or invest, but rather firms. We therefore look at data at the micro (firm or establishment) level to shed light on questions such as: What types of firms are involved in trade or investments? What distinguishes these globalized firms, if anything, from firms that are not engaged in these international activities? What benefits are there for the firms and also their workers? To look at these questions, the first part of the paper provides some insights from the existing literature. We firstly review what has become a substantial literature on exporting activity, using data for German firms. Interestingly, but in a sobering way, studies on imports are far less prolific. This knowledge gap is most likely due to a lack of data on import activities of firms. We also look at some studies that investigate the implications of inward investment, or foreign ownership, as well as outward investment by German multinational enterprises (MNEs) at the firm level. In Section 3 of the paper we then use establishment data to provide some more recent evidence on these relationships. While our data easily cover the activities of exporting and foreign ownership, a clear definition of outward investment by German MNEs is more difficult. Information on import activities is not at all available in our data set, the IAB Betriebspanel, which we describe in more detail below. We describe the participation of establishments in international activities. Additionally, we estimate performance premia for establishments engaged in these activities. Finally, we also investigate whether firms starting these activities experience performance improvements as a result. By “performance” we mean establishment productivity and innovation activity, but also employment, wages and skill structure of establishments in order to say something about workers in these types of firms. In the final part of the paper we summarize the main findings, both from our own work and the existing literature, and offer some conclusions.
Keywords: 330